Steinbuch’s Epistemological Model and the Reality of Particles: A Philosophical Perspective for Chemistry Education - Almubarak Almubarak; Nahadi Nahadi; Galuh Yuliani; Corrienna Abdul Talib; Dini Noor Arini (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Atoms are considered entities that independently originate from human thought and perception based on a materialist perspective. In terms of the scientific model concept, Steinbuch (1977) created a scheme to indicate the epistemological process in science called “thinking in model terms.” This scheme is the basis for understanding matter as reality. The purpose of the study is to explain the philosophical review of the study of the concept of particles as matter. This review can make students and teachers aware of the importance of a thinking model for understanding science. The implementation of the study used “reviewing the literature” with theoretical interventions from various literatures through five stages, namely identifying vital terms, locating literature, critically evaluating and selecting the literature for your review, organizing the literature, and writing a literature review. The study results show that a philosophical review of the understanding of particles as matter that is real is an essential component of holistically understanding science. Understanding based on Steinbuch's scheme, “thinking in model terms,” significantly impacts civilization, including chemistry education. The scheme's application also trains participants' representational abilities, especially at the particulate level, so that the chemistry knowledge obtained is meaningful to participants.